Preparation of semiconductor ZnO powders by sol-gel method: Humidity sensors - Ates, T.; Tatar, C.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2013)
Undoped and Sn-doped ZnO nanopowder samples were prepared by the sol-gel method. The crystalline structure and surface morphology of the samples were analyzed by X-ray diffraction and atomic force microscopy. X-ray diffraction results indicate that the samples exhibit a hexagonal crystal structure. Electrical properties of the samples were measured by two probe method. The activation energies of the ZnO samples for low and high temperatures regions were determined. The optical band gaps of the samples were determined by optical absorption method. It was found that the samples have a direct transition optical band gap and the optical band gap values of the ZnO samples were changed with Sn doping. Quartz crystalline microbalance (QCM) technique was employed to investigate sensor features of the ZnO samples. The humidity sensor properties of undoped and Sn-doped ZnO samples based on quartz crystalline microbalance sensors were investigated. The obtained results indicate that the undoped and Sn-doped ZnO nanopowder samples can be used for humidity sensor applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Sensor; Humidity sensor; Quartz crystal microbalance; Nano-structured ZnO